(untitled) - Kirchner, Walter (New York, 1958)
Western civilization since 1500 digests the course of Western history from the beginnings of the "Modern Age" to the present. the book is completely up-to-date and provides a compact, comprehensive source to quick reference and review of facts and events.
Keywords: Civilization, Western,Vawn minh phương tây; History,Lịch sử